Value of 18F-fluorodeoxyglucose positron emission tomography/computed tomography in the evaluation of pulmonary artery activity in patients with Takayasu's arteritis. (13th August 2020) - Gao, Wei; Gong, Juan-Ni; Guo, Xiao-Juan; Wu, Jiao-Yan; Xi, Xiao-Ying; Ma, Zhan-Hong; Yang, Yuan-Hua; Yang, Min-Fu
Abstract: Aims: To explore the value of 18 F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) in the detection of active pulmonary artery (PA) lesions in patients with Takayasu's arteritis (TA). Methods and results: Consecutive TA patients with PA involvement were prospectively recruited. Clinical activity was assessed according to the National Institutes of Health (NIH) criteria. CT pulmonary angiography (CTPA) or magnetic resonance pulmonary angiography was performed for evaluation of vascular structural characteristics, and mural thickening was considered as radiologically active. A vascular segment with 18 F-FDG uptake ≥ liver was considered as PET-active. A total of 38 18 F-FDG PET/CT scans were performed in 29 patients. In terms of disease activity, the sensitivity of 18 F-FDG PET/CT did not significantly differ from radiological imaging (71.4% vs. 92.9%, P = 0.250), but 18 F-FDG PET/CT had higher specificity (91.7% vs. 37.5%, P = 0.001) and accuracy (84.2% vs. 57.9%, P = 0.022). Although the majority of PET-active PA segments (54.9%) showed mural thickening, 14 PA segments with normal structure were also PET-active. 18 F-FDG activity did not significantly differ between the PA and aorta in clinically active patients. In addition, 18 F-FDG activity of the PA was positively correlated with inflammatory markers. Changes in 18 F-FDG activity in PA during follow-up reflected therapeutic effects. Conclusion: 18 F-FDG PET/CT can effectively evaluate PA activity in TA patients, and its diagnostic performance is superior to radiological imaging. The 18 F-FDG activity of PA shows a good correlation with clinical disease status and inflammatory markers and can be used to monitor therapeutic effects.